2022
DOI: 10.1021/acsomega.1c05771
|View full text |Cite
|
Sign up to set email alerts
|

Heat Treatment Effects for Controlling Dye Molecular States in the Hydrophobic Core of Over-1000 nm Near-Infrared (NIR-II) Fluorescent Micellar Nanoparticles

Abstract: Organic molecules that emit near-infrared (NIR) fluorescence at wavelengths above 1000 nm, also known as the second NIR (NIR-II) biological window, are expected to be applied to optical in vivo imaging of deep tissues. The study of molecular states of NIR-II dye and its optical properties are important to yield well-controlled fluorescent probes; however, no such study has been conducted yet. Among the two major absorption peaks of the NIR-II dye, IR-1061, the ratio of the shorter wavelength (900 nm) to the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…IR-1061 dimers and monomers had peaks at approximately 950 and 1070 nm, respectively. 37 The results showed that IR-1061 formed less dimers in PDLLA than in PLLA ( Fig. 2 ), suggesting that IR-1061 showed higher affinity for PDLLA than PLLA.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…IR-1061 dimers and monomers had peaks at approximately 950 and 1070 nm, respectively. 37 The results showed that IR-1061 formed less dimers in PDLLA than in PLLA ( Fig. 2 ), suggesting that IR-1061 showed higher affinity for PDLLA than PLLA.…”
Section: Resultsmentioning
confidence: 92%
“… 24,28 Previous studies have shown that the molecular state of IR-1061 varies between monomer and dimer depending on the polymer and solvent being used, as well as its concentration. 37 In short, IR-1061 is a low polarity molecule that, while it can exist as monomers in environments with high affinity even at locally high concentration, tends to form dimers that show low fluorescence intensity in non-polar and hydrophobic environments. 37 Previous studies have shown that the aggregate formation like dimers of organic dye molecules alters their optical properties such as emission intensity and wavelength.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of the micellar nanoparticles was presumed to be such that the stearoyl group, a fatty acid chain, forms a hydrophobic core, PEG forms a hydrophilic shell, and IR-1061 is encapsulated in the core. Subsequently, many OTN-NIR fluorescent micellar nanoparticles with polymethine dyes encapsulated in various hydrophobic cores, such as DSPE [57,58], other lipids [59], polycaprolactone (PCL) [60], and polystyrene (PSt) [61] have been reported (Fig. 3).…”
Section: Nanoparticles Encapsulating Near-infrared Fluorescent Dyementioning
confidence: 99%